2007
DOI: 10.1089/aid.2007.0112
|View full text |Cite
|
Sign up to set email alerts
|

HIV Proteins Regulate Bone Marker Secretion and Transcription Factor Activity in Cultured Human Osteoblasts with Consequent Potential Implications for Osteoblast Function and Development

Abstract: A high incidence of decreased bone mineral density (BMD) has increasingly been associated with HIV infection. In this study mesenchymal stem cell (MSC) and human osteoblast (hOB) cell lines were treated with HIV tat, HIV rev, HIV p55-gag, HIV gp120 and HTLV env (100 ng/ml, 24 h). Cells were then analyzed for calcium deposition, alkaline phosphatase (ALP) activity, and lipid levels using established methods. Real-time PCR with gene-specific primers was used to quantify the mRNA levels of the transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 33 publications
1
61
0
6
Order By: Relevance
“…In untreated HIV, through direct viral effects and inflammatory effects, bone resorption and bone formation are uncoupled. 10 In vitro studies have shown that HIV viral proteins Vpr and gp120 stimulate osteoclast activity and p55-gag suppresses osteoblast activity and increases osteoblast apoptosis. [11][12][13] In addition, inflammatory cytokines, such as tumour necrosis factor α and interleukin 6 promote osteoclastogenesis and bone resorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In untreated HIV, through direct viral effects and inflammatory effects, bone resorption and bone formation are uncoupled. 10 In vitro studies have shown that HIV viral proteins Vpr and gp120 stimulate osteoclast activity and p55-gag suppresses osteoblast activity and increases osteoblast apoptosis. [11][12][13] In addition, inflammatory cytokines, such as tumour necrosis factor α and interleukin 6 promote osteoclastogenesis and bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…10 In vitro studies have shown that HIV viral proteins Vpr and gp120 stimulate osteoclast activity and p55-gag suppresses osteoblast activity and increases osteoblast apoptosis. [11][12][13] In addition, inflammatory cytokines, such as tumour necrosis factor α and interleukin 6 promote osteoclastogenesis and bone resorption. [14][15][16] High concentrations of HIV RNA have been associated with elevated levels of receptor activator of nuclear factor κ β ligand (RANKL), an osteoblast secreted cytokine that promotes osteoclast formation.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Briefly, treated and control cells were fixed in 70% ice-cold ethanol for 1 h. The cells were then stained with 40 mM alizarin red (Sigma), pH 4.2, for 10 min with gentle agitation and rinsed five times with double distilled water. Alizarin Red S was extracted from fixed cells by 500 mL 10% cetylpyridinum chloride (CPC) treatment for 20 min.…”
Section: Calcium Depositionmentioning
confidence: 99%
“…A infecção pelo HIV por si e/ou associada a estados de ativação imune e inflamatória, pode alterar a osteoclastogênese, aumentando a taxa de apoptose de osteoblastos primários, reduzindo a deposição de cálcio e a atividade da fosfatase alcalina, diminuindo proteínas específicas de osso e comprometendo a diferenciação de células mesenquimais em osteoblastos (O'Brien et al, 2001;Fakruddin;Laurence, 2003;Cotter et al, 2007;Gibellini et al, 2008;Gutierrez;Masiá, 2011).…”
Section: Impacto Da Hiv/aids E Tarv No Crescimento E Desenvolvimento unclassified